2019
DOI: 10.1111/jcmm.14570
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid receptor 1 is involved in renal fibrosis during chronic allograft dysfunction: Proof of concept

Abstract: Chronic allograft dysfunction (CAD), defined as the replacement of functional renal tissue by extracellular matrix proteins, remains the first cause of graft loss. The aim of our study was to explore the potential role of the cannabinoid receptor 1 (CB1) during CAD. We retrospectively quantified CB1 expression and correlated it with renal fibrosis in 26 kidney‐transplanted patients who underwent serial routine kidney biopsies. Whereas CB1 expression was low in normal kidney grafts, it was highly expressed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…A total of 166 kidney graft biopsies was performed in the 66 patients. The biopsies were processed for routine light microscopy, as we previously described 56 . Biopsy samples were fixed in formalin, acetic acid and alcohol (AFA), paraffin-embedded and sliced 2.5 µm thick.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 166 kidney graft biopsies was performed in the 66 patients. The biopsies were processed for routine light microscopy, as we previously described 56 . Biopsy samples were fixed in formalin, acetic acid and alcohol (AFA), paraffin-embedded and sliced 2.5 µm thick.…”
Section: Methodsmentioning
confidence: 99%
“…For each biopsy, the cortical section, defined as the part inside the renal capsule and outside the medulla, was manually selected on digital slides. Glomeruli and medium-sized arteries were deleted by the operator.Renal-cortex fibrosis was quantified using a computer-based morphometric analysis software (Calopix, Tribvn Healthcare, Châtillon France) as previously published 56,57 . Briefly, the operator manually selects internal Sirius Red negative areas and positive areas and next runs the software that show the final selection of the Red area.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that upon transforming growth factor β (TGFβ) stimulation, renal myofibroblasts expressed CB1R and secreted endocannabinoid ligands, whereas CB1R blockade reduced collagen synthesis ( 12 ). During chronic kidney allograft dysfunction (CAD) in humans, we found that CB1R was highly expressed in tubular cells ( 28 ). CAD remains the first cause of graft loss ( 179 ) and corresponds to the progressive and inevitable impairment of renal graft function.…”
Section: The Role Of Cannabinoid Receptors In Chronic Kidney Diseases and Renal Fibrosismentioning
confidence: 99%
“…Most endogenous ligands are ecosanoïds which derive from phospholipids of cellular membranes (24,25). Whereas CB1R expression is low in normal kidneys (12,(26)(27)(28), we previously found that its expression increased in metabolic CKD but also in nonmetabolic CKD such as IgA nephropathy, acute interstitial nephritis, and chronic allograft nephropathy (12,28). Recent studies have demonstrated that CB1R is involved in CKD during diabetes and/or obesity (13,(15)(16)(17)(18) by its role on metabolism but also through a direct action on podocytes and tubules.…”
Section: Introductionmentioning
confidence: 99%